HIV RISKY BEHAVIOURS OF MEN WHO HAVE SEX WITH MEN IN TIRANA - Hallkaj, Elda; Bani, Roland (European Scientific Journal, ESJ, 2015)
HIV infection remains to be of major public health importance in Europe, with evidence of increasing transmission among MSMs. The article presents the findings of the Behavioral and Biological Surveillance Study conducted in Tirana with 198 MSMs, utilizing a respondent-driven sampling. 40.6% of MSM have tried drugs. The overwhelming MSM respondents (90.5%) had anal sex in the past 6 months. Less than half of MSM 45.5% had anal sex with a commercial partner in the 6 months preceding the study. Only half of MSM who have had a commercial sex partner, used a condom with that partner during the last anal sex. On the other hand, even fewer MSM 20.3% used a condom consistently during every anal sex act with a commercial sex partner. Multiple partnerships are frequent, with an estimated 65.2% of MSM who have had sex with a non-commercial partner in the past 6 months having had 2-4 partners. 75.5% in the Tirana MSM network have had sex with a female. Condom use with females at last sex was 40.6 % and only 12% reporting consistent condom use with all female partners in the past 6 months. The majority of MSM (70%) are estimated to know that confidential HIV testing is available in Tirana. The sample characteristics indicate that of those MSM who had been tested, the majority 86.7% taken the HIV test voluntarily. The findings call for development of interventions to target MSMs for improved healthy behaviors.